2023
DOI: 10.3389/fpsyg.2023.1135658
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the academic involution scale for college students in China: An application of Rasch analysis

Abstract: Recent academic attention on educational involution in China underpins the need for a valid and reliable instrument to precisely measure college students’ academic involution behaviors. Seeing the scarcity of a proper instrument, the current study attempted to analyze the item-level psychometric properties of the newly developed Academic Involution Scale for College Students (AISCS) in China by using a Rasch model. A total of 637 college students in a public university in northern China participated in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Therefore, this paper further supports the findings of Ren and other scholars based on field research in the Chinese countryside. In addition, this paper also provides empirical arguments for previous scholars’ conclusions about the restorative effects of soundscapes [ 149 , 150 ]. At the same time, few studies have focused on the association between Rural Soundscape Perception and Environmental Restoration Perception in the context of tourism, and the findings of this study may fill this research gap.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, this paper further supports the findings of Ren and other scholars based on field research in the Chinese countryside. In addition, this paper also provides empirical arguments for previous scholars’ conclusions about the restorative effects of soundscapes [ 149 , 150 ]. At the same time, few studies have focused on the association between Rural Soundscape Perception and Environmental Restoration Perception in the context of tourism, and the findings of this study may fill this research gap.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, it may also bring them substantial academic pressure. Previous studies [ 19 , 24 ] have found a significant positive correlation between academic involution in education and individuals’ anxiety and stress. Academic involution exacerbates competitive pressures among students, increasing their perception of stress [ 25 ].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 96%
“…In addition to relative deprivation, academic involution may also be a mediator between the academic involution atmosphere and stress response [ 19 ]. The term “involution” was initially proposed by American anthropologist Alexander Goldenweiser [ 20 ] to describe a situation where individuals engage in mutual competition and internal depletion for limited resources, which is similar to “vicious competition” and results in a continual decrease in individual’s “gain-to-effort ratio” [ 21 ].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…When we delve into the root causes of parental educational anxiety, we inevitably turn our attention to the phenomenon of educational involution. As pointed out by Yang et al (2023), educational involution in China refers to the situation within the country's education system where students and parents engage in numerous additional academic activities and competitions to secure high-quality educational resources, aiming for better school admissions and future career competitiveness. In this highly competitive environment, students are compelled to participate in various subject competitions, training programs, and extracurricular activities, hoping to excel academically and socially.…”
Section: Gaining Insight Into Educational Involution: Anxiety and Par...mentioning
confidence: 99%